The Therapeutic potential of interferon-gamma in tuberculosis - Svetlana A. Berns; Julia A. Isakova; Polina Pekhtereva (International Association of Physical Chemists (IAPC), 2022)
Tuberculosis is one of the critical health problems worldwide. The search for ways to improve the results of tuberculosis treatment and overcome drug resistance lies in understanding the pathogenesis of the development of the infectious process. The interferon system, particularly the role of interferon-gamma, has been identified as the main link in the immune response in tuberculosis. The clinical efficacy of interferon-gamma has been studied and evaluated in clinical trials since the end of the last century. There was obtained evidence of the clinical efficacy of interferon-gamma as part of complex therapy. Recent experimental data make it possible to consider interferon-gamma as a promising therapeutic option for the treatment of multidrug-resistant tuberculosis as part of complex therapy worthy of further studies.